2006
DOI: 10.1158/0008-5472.can-06-0605
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Selectivity and Specificity of the Proteasome Inhibitors BzLLLCOCHO, PS-341, and MG-132

Abstract: The 26S proteasome is a multicatalytic protease responsible for regulated intracellular protein degradation. Its function is mediated by three main catalytic activities: (a) chymotrypsinlike (CT-L), (b) trypsin-like, and (c) peptidylglutamyl peptide hydrolysing (PGPH). Proteasome inhibition is an emerging therapy for many cancers and is a novel treatment for multiple myeloma. Here, we profile the contributions of the three catalytic activities in multiple myeloma cell lines and compare the specificity and cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
111
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(120 citation statements)
references
References 25 publications
(30 reference statements)
8
111
0
1
Order By: Relevance
“…Higher doses of Bortezomib are required to inhibit CT-L and C-L activity, whereas little, if any, inhibition of T-L activity was noted. Importantly, our study showed that MM cells exhibit higher constitutive levels of T-L proteasome activity than either CT-L or C-L activities (Crawford et al, 2006). These data, coupled with the results that NPI-0052, but not Bortezomib, efficiently inhibits CT-L þ T-L activities (Chauhan et al, 2005a), suggest that NPI-0052 may trigger more proteolysis than Bortezomib in MM cells.…”
supporting
confidence: 64%
See 1 more Smart Citation
“…Higher doses of Bortezomib are required to inhibit CT-L and C-L activity, whereas little, if any, inhibition of T-L activity was noted. Importantly, our study showed that MM cells exhibit higher constitutive levels of T-L proteasome activity than either CT-L or C-L activities (Crawford et al, 2006). These data, coupled with the results that NPI-0052, but not Bortezomib, efficiently inhibits CT-L þ T-L activities (Chauhan et al, 2005a), suggest that NPI-0052 may trigger more proteolysis than Bortezomib in MM cells.…”
supporting
confidence: 64%
“…It is likely that blockade of one or more of these proteasomal activities along with the kinetics of inhibition confer therapeutic advantage. Moreover, previous reports showed that different organs/cell types express different ratios of constitutive-, immuno-, and hybrid-proteasomes (Stohwasser et al, 1997;Dahlmann et al, 2000;Crawford et al, 2006). Our ongoing studies using MM patient cells and a panel of MM cell lines are addressing these questions by designing more sensitive and specific proteasome probes against each proteasome subunits.…”
mentioning
confidence: 97%
“…It has been shown that 3 HLA-A*0201 restricted epitopes (E7 [11][12][13][14][15][16][17][18][19][20] , E7 82-90 and E7 [86][87][88][89][90][91][92][93] ) induce CTL responses in HLA-A*0201 transgenic mice, and the generated CTLs lyse HLA-A*0201 1 HPV-16-positive CaSki cells. 34 As reported by Muderspach et al, 35 increase of E7 epitope-specific reactivity in cytokine release and cytotoxicity assays was demonstrated in 10 of 16 HPV-16-positive HLA-A*0201 1 patients with high-grade cervical or vulvar CIN after vaccination with either E7 [11][12][13][14][15][16][17][18][19][20] or E7 86-93 epitopes, and a proportion of these patients achieved partial clearance of virus infections and regression of lesions. Therefore, we sought to identify HLA-A*2402-restricted CTL epitopes from HPV-16 E6 and E7 oncoproteins by reverse immunology to facilitate immunotherapy for cervical cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…39 Although IFN-g treatment upregulates immunoproteasomes and TAP proteins in CaSki cells, forced expression of E6 by a recombinant vaccinia virus encoding HPV-16 E6/E7 fusion protein was required to render them susceptible to CTL lysis. 39 In contrast, E7 has been shown to be more abundantly expressed than E6 in HPV-16-positive and HPV-18 1 cervical cancer cell lines 40,41 may explain why CTLs specific for 3 HLA-A*0201-restricted E7 epitopes (E7 [11][12][13][14][15][16][17][18][19][20] , E7 82-90 and E7 86-93 ) 36 could kill CaSki cells (HLA-A*0201 1 ). 34 Second, IFN-g gave a marginal effect on E6 mRNA expression, but its favorable effect on increased cell surface expression of HLA class I molecules was evident in most cell lines tested, which is critical for efficient recognition by CD8 1 T cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation